A label‐free DNAzyme‐cleaving fluorescence method for the determination of trace Pb2+ based on catalysis of AuPd nanoalloy on the reduction of rhodamine 6G. (3rd July 2014) - Tang, Meiling; Wen, Guiqing; Luo, Yanghe; Kang, Caiyan; Liang, Aihui; Jiang, Zhiliang
Abstract The substrate chain of double‐stranded DNA (dsDNA) could be specifically cleaved by Pb2+ to release single‐stranded DNA (ssDNA) that adsorbs onto the AuPd nanoalloy (AuPdNP) to form a stable AuPdNP–ssDNA complex, but the dsDNA can not protect AuPdNPs in large AuPdNP aggregates (AuPdNPA) under the action of NaCl. AuPdNP–ssDNA and large AuPdNPA could be separated by centrifugation. On increasing the concentration of Pb2+, the amount of released ssDNA increased; AuPdNP–ssDNA increased in the centrifugation solution exhibiting a catalytic effect on the slow reaction of rhodamine 6G (Rh6G) and NaH2PO2, which led to fluorescence quenching at 552 nm. The decrease in fluorescence intensity (ΔF) was linear to the concentration of Pb2+ within the range 0.33–8.00 nmol/L, with a detection limit of 0.21 nmol/L. The proposed method was applied to detect Pb2+ in water samples, with satisfactory results. Copyright © 2014 John Wiley & Sons, Ltd.